Eco Friendly-Microwave Assisted Extraction of Cellulose from Sugarcane Bagasse - Indah Hartati; Ismiyatul Kholisoh; Suwardiyono Suwardiyono; Laeli Kurniasari; Indah Riwayati (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
Cellulose is widely present in various forms of biomasses. Cellulose and its derivatives have many advantages and have been used for years in a wide variety of applications. Obtaining pure cellulose from lignocellulosic materials is essential due to its potential advantages and applications. Sugarcane bagasse is one of very promising raw materials for cellulose production due to its high cellulose content. The objective of this research was to investigate the microwave assisted extraction of cellulose from sugarcane bagasse by using an eco-friendly solvent, i.e. acetic acid. The microwave assisted extraction of sugarcane bagasse cellulose were conducted in varied extraction time (30-70 minutes) and solid liquid ratio of 1:12-1:20, while the acetic acid concentration was fixed at 5% and the power level of the microwave was set at 39.9 W. The product was analyzed for its alpha, beta and gamma cellulose content. The research showed that 67.56% was the highest alpha cellulose content of the sugarcane bagasse pulp obtained from the eco- friendly microwave assisted extraction conducted at 60 minutes of extraction, solid liquid ratio of 1:12, acetic acid concentration of 5% and microwave power level of 39.9 W. Keywords: sugarcane bagasse, extraction, cellulose